Improved B cell development in humanized NOD‐scid IL2Rγnull mice transgenically expressing human stem cell factor, granulocyte‐macrophage colony‐stimulating factor and interleukin‐3. Issue 4 (28th August 2016) - Jangalwe, Sonal; Shultz, Leonard D.; Mathew, Anuja; Brehm, Michael A.
Abstract : Introduction: Immunodeficient mice engrafted with human immune systems support studies of human hematopoiesis and the immune response to human‐specific pathogens. A significant limitation of these humanized mouse models is, however, a severely restricted ability of human B cells to undergo class switching and produce antigen‐specific IgG after infection or immunization. Methods: In this study, we have characterized the development and function of human B cells in NOD‐ scid IL2Rγ null (NSG) mice transgenically expressing human stem cell factor (SCF), granulocyte macrophage colony‐stimulating factor (GM‐CSF), and IL‐3 (NSG‐SGM3) following engraftment with human hematopoietic stem cells, autologous fetal liver, and thymic tissues (bone marrow, liver, thymus or BLT model). The NSG‐SGM3 BLT mice engraft rapidly with human immune cells and develop T cells, B cells, and myeloid cells. Results: A higher proportion of human B cells developing in NSG‐SGM3 BLT mice had a mature/naive phenotype with a corresponding decrease in immature/transitional human B cells as compared to NSG BLT mice. In addition, NSG‐SGM3 BLT mice have higher basal levels of human IgM and IgG as compared with NSG BLT mice. Moreover, dengue virus infection of NSG‐SGM3 BLT mice generated higher levels of antigen‐specific IgM and IgG, a result not observed in NSG BLT mice. Conclusions: Our studies suggest that NSG‐SGM3 BLT mice show improved human B cell development and permit the generation of antigen‐specific antibody responses to viral infection. Abstract : In this study, we have used the NSG‐SCF/GM‐CSF/IL3 (NSG‐SGM3) strain of mice engrafted with human fetal thymus, liver, and HSC (BLT) to establish a novel humanized mouse model with enhanced human B cell development and function. A higher proportion of human B cells developing in NSG‐SGM3 BLT mice had a mature/naive phenotype with a corresponding decrease in immature/transitional human B cells as compared to NSG BLT mice. Dengue virus infection of NSG‐SGM3 BLT mice generated higher levels of antigen‐specific IgM and IgG, a result not observed in NSG BLT mice.